PERTUMBUHAN DAN HASIL TANAMAN TOMAT(Lycopersicum esculentum Mill.)PADA TANAH GAMBUT PEDALAMAN DENGANPEMBERIAN PUPUK ORGANIK DAN NPK (Application of NPK and Organic Fertilizers on Peat Soil to the Growth and Yield of Tomato (Lycopersicum esculentum Mill.)) - rudin, syah; illah, Kam; jaya, W. R. P, Ren (AGRIPEAT, 2017)
ABSTRACTThe purposed of this experiment were to find out the interaction betweentype of organic fertilizer and dosagesof inorganicfertilizer on peat soil tothe growth and yield oftomato. The experimental units laid onFactorial Completely Randomized Design (CRD) with two factors. The first factor was three types of organic fertilizer i.e: P1: chicken manure (10 ton ha-1); P2: cow manure (10 ton ha-1); P3: compost of palm oil empty fruit bunches (10 ton ha-1). The second factor was dosage of NPK fertilizer which consisted of 4 levels: N0: without fertilizer (control); N1: 100 kg ha-1; N2: 200 kg ha-1; N3: 300 kg ha-1. Variables measured were: plant height, number of leaves, numbers of productive branches and weight of harvested fruit.The results showed that combination of compost with NPK fertilizer doses of 300 kg ha-1 is the best in enhancing vegetative growth of plants, with plant height reaching 84,3 cm and 30 leaf sprigs. In generative phase, combination of chicken manure with the dosage of NPK 300 kg ha-1produces the heaviest tomato harvest weight, which is 379.4 g plant-1. The best dosage of NPK fertilizer in increasing the growth and yield of tomato is 300 kg ha-1.Keywords: tomato, peat soil, organic fertilizer, NPK fertilizer